Legal Challenges in the Implementation of Agrarian Reform in Dayeuhluhur Village, Tempuran District, Karawang Regency - Guntara, Deny; Wahyudi, Rikes; Gunawan, Endang Ano; Rahman, M. Rafly Dwi; Dewi, Cindy Aulia; Putri, Shilva Alya; Putra, Daffa Fauzan Hanif Angkoso (Jurnal Hukum dan Keadilan, 2024)
Agrarian reform is an effort to change the structure of control, ownership, use, and utilization of land to achieve social justice and community welfare. However, the implementation of agrarian reform often faces various obstacles, whether technical, social, political, or legal. In Dayeuhluhur Village, legal factors are one of the main obstacles in the implementation of agrarian reform. This research aims to understand how the land administration system is implemented in Dayeuhluhur Village, Tempuran Subdistrict, Karawang Regency, West Java Province. The method used is empirical juridical, which includes interviews and direct observations in Dayeuhluhur Village, as well as data analysis from literature as supporting material. The collected data is then analyzed qualitatively to explain the findings obtained from observations and data recorded in the journal. Data were collected through primary data sources, such as interviews and observations, as well as secondary data sources, such as documents. The results of this study show that the legal challenges in the implementation of agrarian reform in Dayeuhluhur Village, Tempuran Subdistrict, Karawang Regency include unclear land legal status, complicated bureaucracy, inconsistency of regulations, weak law enforcement, and limited access to legal information and education. Overcoming these challenges requires joint efforts from the government, law enforcement officers, and active community participation to create a more just and sustainable agrarian system.